2019
DOI: 10.1249/mss.0000000000002001
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Exercises Similarly Reduce Older Adults’ Mobility Limitations

Abstract: Introduction/Purpose Little is known about the comparative effectiveness of exercise programs, especially when delivered at a high intensity, in mobility-limited older adults. We compared the effects of 25 sessions of high-intensity agility exergaming (EXE) and stationary cycling (CYC) at the same cardiovascular load on measured and perceived mobility limitations, balance, and health-related quality of life in mobility-limited older adults. Methods Rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…Because exercise duration was the dosing factor in the intervention, which was delivered at a high intensity (rate of perceived exertion can reach ∼16 of 20 [17, 18]), we set the 6-minute walk test (6MWT) as the primary outcome. The 6MWT is a reliable and valid measure of walking capacity that is sensitive to change [19].…”
Section: Methodsmentioning
confidence: 99%
“…Because exercise duration was the dosing factor in the intervention, which was delivered at a high intensity (rate of perceived exertion can reach ∼16 of 20 [17, 18]), we set the 6-minute walk test (6MWT) as the primary outcome. The 6MWT is a reliable and valid measure of walking capacity that is sensitive to change [19].…”
Section: Methodsmentioning
confidence: 99%
“…Five studies evaluated the overall impact of VRSs on BADLs [ 33 , 34 , 35 , 36 , 37 ] and three studies examined IADLs [ 38 , 39 , 40 ]. We also identified six studies which assessed the effectiveness of VRSs on the capacity to make transfers and twenty-one studies which reported on their effectiveness in improving functional ambulation.…”
Section: Resultsmentioning
confidence: 99%
“…As Figure 2 a shows, the effect size of VRSs in improving the performance of BADLs is moderate but significant; the total SMD was 0.61 (95% CI: −0.15; 1.37). Four of the studies which assessed effectiveness on BADLs obtained a large effect (d > 0.8) [ 33 , 34 , 35 , 37 ] and two studies found a medium effect [ 33 , 38 ]. However, the effectiveness of VRSs was smaller for the three studies which assessed IADLs [ 38 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations